2022
DOI: 10.1177/10464964221089836
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Learning and Reciprocity in Interdisciplinary Research

Abstract: While cohesive teams are essential to advancing interdisciplinary research, few frameworks exist to guide team development. In this article, eight academic women adopt a participatory process of inter-relational reflexivity to reflect upon our interdisciplinary research and propose a best-practice framework for sustained effectiveness of interdisciplinary collaboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Although previous research on the translational approach within research teams is scarce, various studies have used qualitative approaches and systematic literature searches to identify factors that are crucial for effective interdisciplinary teamwork (Lorenzetti et al, 2022; Nancarrow et al, 2013; Salas et al, 2005; Tkachenko & Ardichvili, 2020). The factors identified in these studies are remarkably similar, and relate to the hub types identified here in various ways.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although previous research on the translational approach within research teams is scarce, various studies have used qualitative approaches and systematic literature searches to identify factors that are crucial for effective interdisciplinary teamwork (Lorenzetti et al, 2022; Nancarrow et al, 2013; Salas et al, 2005; Tkachenko & Ardichvili, 2020). The factors identified in these studies are remarkably similar, and relate to the hub types identified here in various ways.…”
Section: Discussionmentioning
confidence: 99%
“…The factors identified in these studies are remarkably similar, and relate to the hub types identified here in various ways. First, effective teams need a supportive, encouraging and facilitating leader who listens to team members and establishes a clear vision for the team (Lorenzetti et al, 2022; Salas et al, 2005; Tkachenko & Ardichvili, 2020). Thus, chairs aiming to implement a translational approach should possess these qualities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations